Leandro Erlich - liminal - Camnitzer, Luis 1937-; Cameron, Dan 1956-; Napier, Julia (Malba, 2019)
More than any artist working today, Leandro Erlich (1973, Buenos Aires) has created a body of sculpture and large installations over the past two decades in which the architectural appearance of the everyday functions as a type of perceptual trap, leading he unsuspecting viewer into a visual paradox that systematically defies what should be the rules and order of the material world. Liminalis the first monographic survey exhibition of Erlichs workthroughout the American continent and brings together a selection of twenty-one installations, produced since 1996 to date. The title of the exhibition references a zone that exists at the threshold of another space, suggests a position of being on the verge of crossing over, or entering into, a specific destination or state of existence, but without ever fully getting there. To hover at the liminal edge of an experience suggests that one is perpetually caught between a prior reality that has been left behind, and a new reality beckoning at close range, but leaving us stranded if we were to linger. Over the past two decades, his work has been shown internationally and featured in the permanent collections of major museums and private collectors. He enjoys particular renown in Asia, and his most recent exhibitions at the MORI Art Museum (Tokyo, 2017) and the HOW Art Museum (Shanghai, 2018) have attracted hundreds of thousands of visitors. On June his new show Próximamenteopens at the Ruth Benzacar Gallery in Buenos Aires, followed by LIMINAL. On July, he will become the first non-Chinese artist to occupy the entire exhibition space at the CAFAM (Central Academy of Fine Arts, Beijing), Chinas premiere museum, with the show The Confines of The Great Void
Titelblatt auf Seite [43]. - Exposición: "Leandro Erlich. Liminal" Del 5 de julio al 27 de octubre de 2019 (Créditos)
Keywords: Erlich, Leandro -- 1973-; Erlich, Leandro / 1973- / Exhibitions; Installations (Art) / Exhibitions; Visual perception in art / Exhibitions; Erlich, Leandro / 1973-; Installations (Art); Visual perception in art; Exhibition catalogs; Ausstellungskatalog -- Museo de Arte Latinoamericano -- 05.07.2019-27.10.2019 -- Buenos Aires